Furikake processing training to enhance product quality with innovative technology - I Gusti Ayu Wita Kusumawati; Ida Bagus Agung Yogeswara; Putu Wida Gunawan; Ni Wayan Nursini (University of Merdeka Malang, 2024)
Sathya Sai Primary School provides a variety of extracurricular activities that students can choose from. The Scientific Work Group is one of the extracurricular activities at SD Sathya Sai. SD Satya Sai's Scientific Work Group innovated furikake made from sea lettuce. They won a gold medal in a national event through this processed innovation. The furikake produced by the partners has a slightly bitter taste and durability of only 2 weeks. The purpose of this PKM (community service) activity is to process furikake that is not bitter and has a long product durability. The method used in this activity is training and mentoring. This PKM activity resulted in an increase in partners' understanding of how to process furikake and use appropriate technology tools provided by the PKM team and an increase in furikake durability. In addition, this activity also increased the number of processed innovative products made from sea lettuce. With this PKM activity, it is hoped that the SD Sathya Sai Scientific Work Group can produce other innovative products made from sea lettuce using appropriate technology tools that have been provided by the PKM team.